Pemetaan Persebaran Jenis Lahan Pertanian Berbasis Sistem Informasi Geografis Di Kecamatan Taluditi - Sahriyanto Maku; Sunarty Sully Eraku; Masruroh Masruroh (Universitas Negeri Gorontalo, 2026)
Taluditi District, as an agrarian area, has extensive agricultural land potential; however, spatial information on the distribution of agricultural land types remains limited, hindering effective land management planning. The use of Geographic Information Systems (GIS) is essential to provide accurate spatial data for decision-making processes. This study aimed to map the distribution of agricultural land types using a GIS-based approach in Taluditi District. A descriptive quantitative approach was employed using secondary data, including administrative maps, land use maps, and satellite imagery obtained from official institutions. Data were collected through documentation techniques, while analysis involved land classification and overlay methods using ArcGIS software. The results indicated that agricultural land distribution consisted of three main types: dry fields, plantations, and paddy fields, with spatial patterns influenced by topography and water availability. Dry fields dominated the area at 72%, primarily located in hilly regions, while plantations accounted for 24% with a heterogeneous distribution, and paddy fields comprised only 4% concentrated in lowland areas. Spatially, higher concentrations of agricultural land were found in the central to southern parts of the district, characterized by relatively flat geomorphological conditions. These findings demonstrate a significant relationship between physical landscape characteristics and land use patterns. In conclusion, the agricultural system in Taluditi District is predominantly characterized by dryland farming influenced by topographical conditions and limited water resources. This study provides important implications for sustainable, spatial-based agricultural land management planning.